TS 825 İklimsel verilerinin farklı derece gün bölgeleri için uygunluğunun değerlendirilmesi - Aksoy, Ufuk Teoman; Ekici, Betül Bektaş (My University, 2013)
Solar radiation is an important parameter which is used in building energy simulations especially in solar heat gain calculations of windows. Although the climatic parameters are considered comprehensively in Building Energy Performance Regulations and its appendix BEP-TR calculation method, TS 825 Thermal Insulation Requirements for Buildings is still in effect and proposes the usage of the same solar radiation data in different climatic regions. In this study the solar radiations of vertical surfaces were calculated numerically for sample cities from each of the degree day regions according to TS 825 (Antalya (1st region), Istanbul (2nd region), Elazığ (3rd region) and Kayseri (4th region)). The annual heating energy requirements of buildings having three different form factors and nine different transparency ratios were calculated with the calculated solar radiation and long-term monthly average outdoor temperature values obtained from Turkish State Meteorological Service for four different cities. The obtained energy requirements were compared with annual heating energy requirements of the same building samples calculated with the climatic data given by TS 825 and the appropriateness of the standard for different degree day regions was evaluated.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Güneş ısısı kazancı; Güneş ışınımı; Biçim faktörü; Saydamlık oranı; TS 825